Análise do principais fluxos aéreos dos aeroportos da capital mineira e suas recentes transformações / Analysis of the main aerial flows of the airports of the mining capital and its recent transformations - Alexandre Magno Alves Diniz; Leoni Carlos Alvarenga Diniz (Sociedade & Natureza)
The present paper analyses the intensity and direction of air flows referring to the main BeloHorizonte´s airports, in order to identify their influence areas, such as the economic importancethat these airports represent to the State´s development process. The Alternative Model of the Urban Trip Generation is used as a support, helping the comprehension of the changingsexperimented by the Minas Gerais´ air sector, according to the demand of the air transportation ofpassengers and cargo, focusing at the main causes and consequences of the regular commercialflights´ recent transfer from Belo Horizonte Airport (Pampulha) to Tancredo Neves InternationalAirport (Confins). The comparative data and analyses referring to the air flows of the main BeloHorizonte´s airports, according to the origins and destinations, are processed and mapped, inorder to facilitate the identification of the influence areas of these airports. The results show thatthe Belo Horizonte´s airports have a strong relationship to the airports of the cities São Paulo andRio de Janeiro, showing the dependence of the Belo Horizonte air sector with these locations.